2016
DOI: 10.1071/py14120
|View full text |Cite
|
Sign up to set email alerts
|

Health assessments for Indigenous Australians at Orange Aboriginal Medical Service: health problems identified and subsequent follow up

Abstract: This study aimed to document the types, management and follow up of health issues identified by all Aboriginal Health Assessments (AHA) performed at Orange Aboriginal Medical Service from 1 January 2011 to 31 December 2012. This was done with a retrospective audit of clinical records. In total, 1169 AHAs were performed: 41% child, 53% adult and 6% older person AHAs. Newly identified health issues were documented in 85% (984). Being overweight (41%; 476) and smoking (26%; 301) were the common risk factors ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Receipt of Health Assessment for Aboriginal and Torres Strait Islander People (MBS item 715) by CVD and CVD risk factors, general health status and GP use: proportions, odds ratios and 95% confidence intervals Aboriginal and Torres Strait Islander health checks follow-up care (e.g. review of abnormal results, ongoing management and referral) 24,30 will be essential for preventing further CVD events. The Australian Government introduced a Medicare item specifically targeting absolute CVD risk assessment (MBS item 699 and 77) for use across the general population in April 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Receipt of Health Assessment for Aboriginal and Torres Strait Islander People (MBS item 715) by CVD and CVD risk factors, general health status and GP use: proportions, odds ratios and 95% confidence intervals Aboriginal and Torres Strait Islander health checks follow-up care (e.g. review of abnormal results, ongoing management and referral) 24,30 will be essential for preventing further CVD events. The Australian Government introduced a Medicare item specifically targeting absolute CVD risk assessment (MBS item 699 and 77) for use across the general population in April 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Biddle recommends taking the most efficient approach possible to data collection and analysis in order to minimise participant burden. 180 In summary, research data published in the last five years and indexed on PubMed, 107 Aboriginal health liaison 8,041 b No O'Connor et al 115 Chlamydia 7,103 b Yes Dutton et al 170 Health 128 Albuminuria 860 No Lopez et al 114 Ischaemic heart disease 833 b Yes Hopkins et al 105 Psychological resilience 677 No Arjunan et al 106 Tobacco use 663 No Jamieson et al 164 Oral 113 Stressful events in children 344 b No Lalla et al 103 Oral mucosal disease 342 No Radford et al 104 Dementia 336 No Whish-Wilson et al 99 Birth outcomes 301 Yes Roberts-Thomson et al 117 Oral health 251 No Dorrington et al 174 Pap smears 213 No Gardener et al 102 Children 205 No Wong et al 126 Midwifery 177 Infant health 175 Yes Luke et al 181 Suicidal 169 Breast feeding 159 Yes Webster et al (Gudaga study) 166 Child growth 157 No Scott et al 110 Sexual health 155 No Miller et al (Gudaga study) 118 Child language assessment 150 No Arrow 100 Oral …”
Section: Sparse Research In Urban Populationsmentioning
confidence: 99%
“…207,209 However, one research paper, published in 2015, conducted in a regional Aboriginal community controlled health service found that many of the problems identified by clinicians conducting Aboriginal and Torres Strait Islander HAs in primary care were either fully (26%) or partially (49%) resolved six months later. 170 The authors considered health problems to be resolved when referrals, immunisations, review of growth, and follow up investigations were attended to. 170 This study provides evidence to suggest that HAs can help identify and facilitate the appropriate management and follow up of various health concerns.…”
Section: Aboriginal and Torres Strait Islander Health Assessments In mentioning
confidence: 99%
See 2 more Smart Citations